PLASMA TREATMENT IMPACT ON PHYSICAL AND CHEMICAL PROPERTIES OF POLYMERIC FIBERS - Radim Hlůžek; Zdeněk Prošek; Jan Trejbal; Josef Fládr; Štepán Potocký (Acta Polytechnica CTU Proceedings, 2017)
Presented work focuses on chemical and physical properties of plasma modified polymeric macro-fibers. Polyethylene terephthalate (PET) and polypropylene (PP) fibers having approx. 300 μm in diameter were modified using cold oxygen plasma in order to achieve their surface changes needed for durable bond and adhesion with cement matrixes. A duration of plasma modification differed between 5 to 480 seconds, where an effect of the treatment was examined. Fiber surfaces chemical changes were researched via wettability measurement with demineralized water (the measurement was repeated immediately and after 1, 7 and 30 days to find out the changes stability). Physical changes were studied by means of weight balance (determination of weight loss) and tensile strength tests. It was found that wettability was enhanced significantly – up to two times, while mechanical properties of treated fibers decreased only slightly.